The impact of the 2008 crisis on UK prices: what we can learn from the CPI microdata - Huw David Dixon; Kul B. Luintel; Kun Tian (Cardiff University, Cardiff Business School, 2014)
This paper takes the locally collected price-quotes used to construct the CPI index in the UK for the period 1996-2013 to explore the impact of the crisis on the pricing behavior of firms. We develop a time-series framework which is able to capture the link between macro- economic variables (in?ation and output) and the behavior of prices in terms of the frequency of price change, the dispersion of price levels and the dispersion of price-growth. Whilst these effects are present, they are small and do not have significant effects for monetary policy.
Keywords: E50; 330; Price-spell; steady state; duration